Urologist Practice Structure and Quality of Prostate Cancer Care. Issue 5 (13th September 2020) - Modi, Parth K.; Yan, Phyllis; Hollenbeck, Brent K.; Kaufman, Samuel R.; Borza, Tudor; Skolarus, Ted A.; Schroeck, Florian R.; Ryan, Andrew M.; Shahinian, Vahakn B.; Herrel, Lindsey A.
Abstract: Introduction: We examined 3 aspects of urologist practice structure that may affect quality of prostate cancer care, including practice size, ownership of an intensity modulated radiation therapy device and participation within a multispecialty group. Health care reforms focused on improving quality are particularly relevant for prostate cancer given its prevalence and concerns for over diagnosis and overtreatment. Methods: Using data from the Surveillance, Epidemiology, and End-Results–Medicare linked registry we examined quality of prostate cancer treatment according to each treating urologist's practice size, type (single specialty vs multispecialty group) and ownership of intensity modulated radiation therapy device. Mixed models were used to adjust for patient differences. Results: We identified 22, 412 men with newly diagnosed prostate cancer treated by 2, 199 urologists during the study. We observed minimal differences for most quality metrics according to practice size, type and ownership of intensity modulated radiation therapy device. Adherence to all eligible quality metrics was better among multispecialty groups compared to single specialty groups (20.0% adherence vs 18.2%, p=0.01) whereas there was no significant difference by ownership of intensity modulated radiation therapy device (17.1% adherence in owners vs 18.9% non-owners, p=0.09). Conclusions: Differences in quality across practice size, type and ownership of intensity modulated radiation therapy device were modest with substantial room for improvement regardless of practice structure.